2016
DOI: 10.1002/2015jb012749
|View full text |Cite
|
Sign up to set email alerts
|

Direct observations of damage during unconfined brittle failure of Carrara marble

Abstract: To observe and quantify the production of microfracturing from initial yield to failure, we deformed Carrara marble samples in uniaxial compression at 20, 105, and 180°C and continuously observed a region of about 1 mm2 on an exposed face with a long‐working distance microscope. Using image processing and microscale strain‐mapping techniques, we measured local strains over a length scale of tens of micrometers. By treating the images with various filters, we identified linear damage features, as well as the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 98 publications
3
27
0
Order By: Relevance
“…Our results are consistent with other studies on the deformation of Carrara marble under uniaxial or triaxial compressive stress conditions (Tal et al, 2016;Wawersik & Fairhurst, 1970;Wong & Einstein, 2009). Twodimensional strain maps obtained from uniaxial tests on marble (Tal et al, 2016) were decomposed into shear and normal components. The normal and shear components of strain were localized along narrow and diagonal features interpreted as microfractures.…”
Section: 1029/2019jb017381supporting
confidence: 93%
“…Our results are consistent with other studies on the deformation of Carrara marble under uniaxial or triaxial compressive stress conditions (Tal et al, 2016;Wawersik & Fairhurst, 1970;Wong & Einstein, 2009). Twodimensional strain maps obtained from uniaxial tests on marble (Tal et al, 2016) were decomposed into shear and normal components. The normal and shear components of strain were localized along narrow and diagonal features interpreted as microfractures.…”
Section: 1029/2019jb017381supporting
confidence: 93%
“…This correlation suggests that regions of high volumetric strain and high shear strain share a common origin, which we attribute to the nucleation, growth, opening, and closing of microfractures and the coupling between them. The postfailure tomogram shows that a higher number of microfractures formed inside grains and propagated across grain boundaries, rather than developing along grain boundaries, in contrast with the behavior observed in Carrara marble (26). The fractures were oriented preferentially toward the direction of the largest compressive stress which is consistent with other studies of similar crystalline rocks (10,11).…”
Section: Dynamics Of Strain Evolutionsupporting
confidence: 87%
“…2. (Inset) The evolution of α toward failure. events and between left-/right-lateral shear events may occur in the form of conjugate microseismicity and faulting or distributed deformation near complex fault geometries, as well as in the surrounding volume (26,39). High-resolution earthquake catalogs in well-instrumented areas show that ongoing seismicity can occur in zones with width of the order of 10 km around major faults (1,3).…”
Section: Implications For Failure In Continental Rocks and Earthquakementioning
confidence: 99%
“…The mean of the dilatational strain population increased by larger magnitudes than the shear strain throughout these experiments, suggesting the greater importance of the micromechanisms that produce local dilation rather than shear. Tracking the 2D strain field on the surface of Carrara marble loaded in uniaxial compression also reveals the dominance of shear and dilatational strain events throughout loading, with a greater frequency of dilatational events near macroscopic failure (Tal et al, 2016). DVC analyses on laminated Green River shale (McBeck et al, 2018) provide a different partitioning of the strain modes than observed in the experiments on marble, sandstone and basalt.…”
Section: Brittle Failure Processes In Rocksmentioning
confidence: 82%